Enantioselective Nazarov cyclization catalyzed by a cinchona alkaloid derivative. Issue 23 (3rd June 2015) - Huang, Yu-Wen; Frontier, Alison J.
Graphical abstract: Abstract: Nucleophilic catalysts for a 1, 6 addition/Nazarov cyclization/elimination sequence were evaluated for their ability to induce enantioselectivity in the electrocyclization step. Of the tertiary amines examined, it was found that a cinchona alkaloid derivative was able to generate substituted 5-hydroxy γ-methylene cyclopentenones with excellent enantioselectivity. The study results suggest that successful cyclization depends upon the ability of the dienyl diketone substrate to readily adopt an s - cis conformation.